Answer:
x/ y = -2/ 3
Step-by-step explanation:
we have:
3(x + y) = y
distributing 3 within the parenthesis:
=> 3x + 3y = y
taking y to the other side, changing its sign in the process
=> 3x = y - 3y
=> 3x = y(1 - 3)
=> 3x = -2y
you can represent any integer as a fraction by putting a "1" in the denominator
![\implies \mathsf{ (3x)/(1) = - (2y)/(1) }](https://img.qammunity.org/2022/formulas/sat/high-school/o4qm471qb499argd6963k8od2196l3s6zl.png)
taking y to the denominator on the LHS and 3 to the denominator on the RHS
![\implies \mathsf{ (x)/(y) = - (2)/(3) }](https://img.qammunity.org/2022/formulas/sat/high-school/qyhzm1wuo5pq2fpemp3p9j3i2lui44vm6a.png)
that makes the ratio, x/y = -2/ 3
______________
Hope this helps!